The Controversy about Education for Citizenship: The Contested Limits of Tolerance in Spain - Burchianti, Flora; Zapata-Barrero, Ricard (SocietàMutamentoPolitica, 2016)
Education is of crucial importance to ensure social cohesion and progress in a given society. Even if the content of citizenship education has been a matter of debate in several European countries, it has taken a singular development in Spain. The important controversy that has been triggered by its introduction in secondary school curriculum is a matter of interrogation: Why did Spain react differently than other European countries? The argument put forward in this article is that education for citizenship reveals the impossibility for Spain to provide a stabilised and consensual definition of national values and identity, precisely because the country is characterised by unresolved questions about its territorial and national diversity, and exemplifies multiple diversity challenges. After providing a European contextualisation of questions of religious and values teaching in Spain, we present a chronology of the controversy and then analyse the public debate in terms of limits to tolerance. We will show that the question of the shared public values highlighted by this conflict is still unsolved and remain non-consensual in the Spanish society.